GsΛ Continuous Function in Topological Space. (26th February 2013) - Missier, S. Pious; Raj, Vijilius Helena
Abstract : We introduce the different notions of a new class of continuous functions called generalized semi Lambda (gsΛ ) continuous function in topological spaces. Its properties and characterization are also discussed.